2006
DOI: 10.1089/aid.2006.22.979
|View full text |Cite
|
Sign up to set email alerts
|

Detection of HERV-K(HML-2) Viral RNA in Plasma of HIV Type 1-Infected Individuals

Abstract: Approximately 8% of the human genome sequence is composed by human endogenous retroviruses (HERVs), most of which are defective. HERV-K(HML-2) is the youngest and most active family and has maintained some proviruses with intact open reading frames (ORFs) that code for viral proteins that may assemble into viral particles. Many HERV-K(HML-2) sequences are polymorphic in humans (present in some individuals but not in others) and probably many others may be unfixed (not inserted permanently in a specific chromos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
105
1
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 85 publications
(111 citation statements)
references
References 26 publications
4
105
1
1
Order By: Relevance
“…We next asked whether expression of HIV-1 viral proteins increases the production of transmissible HK2 VLPs. The rationale behind this approach is that HIV infection, specifically the expression of the HIV-1 Tat and Vif proteins, has been found in previous studies to enhance expression of HK2 (9,10,24,26,27,85,86). Expression of HIV-1 Tat and Vif, but not Vpu, in NCCIT cells increased the production of transmissible HK2 VLPs containing the Bogota probe, as determined by measuring the number of G418-resistant clones (Fig.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…We next asked whether expression of HIV-1 viral proteins increases the production of transmissible HK2 VLPs. The rationale behind this approach is that HIV infection, specifically the expression of the HIV-1 Tat and Vif proteins, has been found in previous studies to enhance expression of HK2 (9,10,24,26,27,85,86). Expression of HIV-1 Tat and Vif, but not Vpu, in NCCIT cells increased the production of transmissible HK2 VLPs containing the Bogota probe, as determined by measuring the number of G418-resistant clones (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…These viruses, however, are widely considered to be noninfectious (15,(20)(21)(22)(23). In addition to the findings of HERV-K expression in cancer cell lines, we have found HK2 RNA, proteins, and VLPs in the blood of patients with HIV-1 infection, lymphoma, and breast cancer (9,10,(24)(25)(26)(27); the capacity of these viruses to package HK2 sequences and transmit them to other cells remains to be tested.…”
mentioning
confidence: 85%
“…In addition, some HERV have been shown to be associated with some autoimmune diseases and cancers (20,21). In certain circumstances, exogenous retrovirus infections such as HIV-1 have been shown to induce HERV-K expression (6,7,11). We have previously shown that HIV-1-infected adults can mount anti-HERV-specific T cell responses and that an inverse relationship exists between the magnitude of the HERV-specific T cell response and the level of HIV-1 viremia in untreated patients, in both the early (10) and the chronic (23) phases of the disease.…”
mentioning
confidence: 97%
“…Additionally, external stimuli, such as infections, viral transactivators, chemical exposures, cytokines, hormones, and inflammation, can induce expression of these proviruses (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46). We and others have shown that HIV-1 infection is associated with increased HERV-K (HML-2) expression in vitro and in vivo (33,(45)(46)(47)(48)(49)(50)(51)(52)(53). Compared to healthy individuals, HIV-1-infected individuals show high levels of HERV-K (HML-2) RNA, DNA, protein, and viral particles in their plasma (45,47,48,50).…”
mentioning
confidence: 99%
“…We and others have shown that HIV-1 infection is associated with increased HERV-K (HML-2) expression in vitro and in vivo (33,(45)(46)(47)(48)(49)(50)(51)(52)(53). Compared to healthy individuals, HIV-1-infected individuals show high levels of HERV-K (HML-2) RNA, DNA, protein, and viral particles in their plasma (45,47,48,50). This HIV-1-mediated activation of HERV-K (HML-2) is partially due to the HIV-1 Tat protein activating the NF-B and NF-AT transcription factors, which then interact with the HERV-K (HML-2) LTR promoter to stimulate transcription (46).…”
mentioning
confidence: 99%